STATISTICAL ANALYSIS OF THE FURNITURE BOARD MANUFACTURING PROCESS FOR THE PURPOSE OF QUALITY IMPROVEMENT - Kushpit, Andriy; Kostyuk, Volodymyr; Kushpit, Oleksandra (Forestry, Forest, Paper and Woodworking Industry, 2024)
The process of manufacturing furniture board using statistical methods is analysed.